Diagnosis of Ehlers-Danlos Syndrome in an Adolescent Who Presents with Recurrent Pneumothoraces and Hemoptysis - Jung, Myung Sun; Pirot, Anayansi Lasso-; Kotwal, Nidhi (Archives of Clinical and Medical Case Reports, 2024)
This is a case report describing a 17-year-old, non-smoker, adolescent male with a history of asthma who was initially evaluated for chronic cough, dyspnea, hemoptysis, and recurrent pneumothoraces requiring multiple chest tube placements and eventually was diagnosed with vascular Ehlers- Danlos Syndrome (EDS) via genetic testing. It is challenging to establish a diagnosis, especially in pediatric patients who do not have a known family history of vascular EDS. This case report emphasizes the importance of high clinical suspicion to make an early diagnosis to inform the patient and family of the prognosis of this condition and to coordinate the specialty care for future management.